Phase-induced intensity noise reduction with improved group velocity dispersion tolerance in SAC-OCDMA systems - Al-Khafaji, Hamza M. R.; S.A., S. A. Aljunid; Amphawan, Angela; Fadhil, Hilal A.; M. Safar, Anuar (Engg Journals Publications, 2013)
The demand for efficient optical communication systems has fuelled considerable research in developing techniques for eradicating phase-induced intensity noise (PIIN) in spectral-amplitude coding optical code-division multiple-access (SAC-OCDMA). This paper investigates the use of modified-AND subtraction detection technique to mitigate PIIN in SAC-OCDMA systems.The simulation results show that the modified-AND subtraction detection demonstrates better performance over the conventional AND detection approach.Furthermore, we have found that, from a transmission length of 40 km onwards, group velocity dispersion (GVD) degrades SAC-OCDMA system performance apparently.Dispersion compensating fiber (DCF) is used to lessen the influence of GVD caused by single mode fiber (SMF).